2022
DOI: 10.1007/s00436-022-07673-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent metabolomic developments for antimalarial drug discovery

Abstract: Malaria is a parasitic disease that remains a global health issue, responsible for a significant death and morbidity toll. Various factors have impacted the use and delayed the development of antimalarial therapies, such as the associated financial cost and parasitic resistance. In order to discover new drugs and validate parasitic targets, a powerful omics tool, metabolomics, emerged as a reliable approach. However, as a fairly recent method in malaria, new findings are timely and original practices emerge fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…When parasites are under significant stress and cannot compensate, cascading reactions that affect multiple systems including metabolic pathways occur [ 46 ]. Given the considerable inhibitory effect of ATS on the glycolytic pathway of parasites and the interference of ATS with various physiological processes of parasites, we next investigated the impact of ATS on the metabolome of parasites using untargeted metabolomics analysis (Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…When parasites are under significant stress and cannot compensate, cascading reactions that affect multiple systems including metabolic pathways occur [ 46 ]. Given the considerable inhibitory effect of ATS on the glycolytic pathway of parasites and the interference of ATS with various physiological processes of parasites, we next investigated the impact of ATS on the metabolome of parasites using untargeted metabolomics analysis (Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…MMV000634 could form interactions with amino acid residues of the AdFUEBP homology model, including hydrophobic interactions and hydrogen bonds. From previous studies, MMV000634 (PubChem CID 16018313; Kim et al, 2021) showed antiplasmodial activity with IC50 at 0.56 μM against the trophozoite stage (PubChem Bioassay AID 1189127) via the alpha‐linolenic acid pathway in lipid metabolism (Mamede et al, 2022). This compound might be able to inhibit the activity of AdFUEBP to hamper Plasmodium development in Anopheles mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are the workflow stages relatively uniform, but so are the extraction methods and solvents, including the data acquisition methods (Vincent & Barrett, 2015). The methods explored in this protocol have generally been used to study other pathogens as well, with differences pertaining to handling the culture, sampling, and data interpretation (Fall et al., 2022; Kafsack & Llinás, 2010; Mamede et al., 2022; Vincent & Barrett, 2015). Metabolomics as an approach is useful regardless of the parasite being studied, and needs only to be adapted to their lifeform, stage, number, and culture conditions.…”
Section: Introductionmentioning
confidence: 99%